Pengaruh Kinerja Keuangan dan Mekanisme Corporate Governance terhadap Manajemen Laba - Wafa Khairani; Noer Sasongko; Andy Dwi Bayu Bawono (Universitas Muhammadiyah Jakarta, 2022)
This study aims to examine the effect of financial performance and corporate governance on earnings management. The research population is all manufacturing companies listed on the Indonesia Stock Exchange, which are 176 companies. With the purposive sampling method for the year 2017-2019, we got the sample of 44 companies with a total of 132 observations. Multiple linear regression was employed for data analysis. The results show that financial performance as proxied by profitability and leverage, partially, has a significant effect on earnings management. Financial performance as proxied by the liquidity ratio has no effect on earnings management. Corporate governance as proxied by managerial ownership, institutional ownership, and the proportion of independent commissioners, partially, has no effect on earnings management.